Protective effect of traditional Chinese medicine on non-alcoholic fatty liver disease and liver cancer by targeting ferroptosis - Wu, Qiongbo; Chen, Zihao; Ding, Yi; Tang, Yunting; Cheng, Yawei (Frontiers in Nutrition, 2022)
Non-alcoholic fatty liver disease (NAFLD) is a chronic liver disease with high incidence and is closely related to metabolic syndrome. If not controlled, it may eventually become hepatocellular carcinoma (HCC). Programmed cell death (PCD) is thought to be a critical role in the disease spectrum of NAFLD. Ferroptosis, a non-apoptotic form of PCD, promotes the early occurrence and development of NAFLD or inhibit the deterioration of HCC. The excess iron ions facilitate the production of reactive oxygen species (ROS), thereby causing damage to cells or tissues. Some studies have demonstrated that many drugs inhibit ferroptosis and protect liver steatosis or carcinogenesis. Traditional Chinese medicine (TCM) has the advantages of multi-target, multi-channel, stable structure and high safety. A variety of active ingredients in TCM regulate ferroptosis. In this review, we summarize the TCM intervention mechanism and application affecting NAFLD/ via regulation of ferroptosis. This article demonstrates the importance of studying ferroptosis to elucidate the mechanisms underlying the different stages of NAFLD and to explore therapeutic measures, and suggests promising directions for the application of TCM, providing ideas and information for the future development of NAFLD or metabolic-related diseases.